The Effects of Public Funding and Entrepreneurial Literacy on The Quality of Learning in Productive Subjects at State Vocational High School 1 Mempawah Hulu, Landak Regency - Elpia Elpia; Nuraini Asriati; Maria Ulfah (Journal of Social Research, 2026)
This study aimed to analyze the effects of public funding and entrepreneurial literacy on the quality of learning in productive subjects at SMK Negeri 1 Mempawah Hulu, Landak Regency, both partially and simultaneously. This research employed a quantitative approach with an associative-causal (explanatory) design. The population consisted of 526 students, from which a sample of 84 eleventh-grade students from six study programs was determined using the Slovin formula and selected through proportionate stratified random sampling. Data were collected through questionnaires and analyzed using multiple linear regression, including classical assumption tests, partial (t-test) and simultaneous (F-test) hypothesis testing, and the coefficient of determination (R²). The results showed that public funding had a positive and significant effect on the quality of learning in productive subjects, and entrepreneurial literacy also had a positive and significant effect on learning quality. Furthermore, public funding and entrepreneurial literacy simultaneously had a positive and significant effect on the quality of learning in productive subjects, explaining 76.8% of its variance, while the remaining 23.2% was influenced by other factors outside the scope of this study. These findings indicated that effective management of public funding and the strengthening of students’ entrepreneurial literacy were important factors in improving the quality of learning in productive subjects.